Proceedings of the 2012 BELIV Workshop: Beyond Time and Errors - Novel Evaluation Methods for Visualization 2012
DOI: 10.1145/2442576.2442580
|View full text |Cite
|
Sign up to set email alerts
|

Toward mixed method evaluations of scientific visualizations and design process as an evaluation tool

Abstract: In this position paper we discuss successes and limitations of current evaluation strategies for scientific visualizations and argue for embracing a mixed methods strategy of evaluation. The most novel contribution of the approach that we advocate is a new emphasis on employing design processes as practiced in related fields (e.g., graphic design, illustration, architecture) as a formalized mode of evaluation for data visualizations. To motivate this position we describe a series of recent evaluations of scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…However, not only the judgment of domain experts but also that of visual experts such as artists, graphic designers, or illustrators can be useful as has been shown in a few cases [1,27,29,30]-in particular since 'critique' as a technique originated from teaching in the visual arts [35]. In visualization, it can be used in combination with techniques such as sketching and ideation when developing new visualization techniques [26]. For evaluating the impact of visualization tools on practices of real users, specific forms of case studies have been suggested [62].…”
Section: Novel Evaluation Methodsmentioning
confidence: 99%
“…However, not only the judgment of domain experts but also that of visual experts such as artists, graphic designers, or illustrators can be useful as has been shown in a few cases [1,27,29,30]-in particular since 'critique' as a technique originated from teaching in the visual arts [35]. In visualization, it can be used in combination with techniques such as sketching and ideation when developing new visualization techniques [26]. For evaluating the impact of visualization tools on practices of real users, specific forms of case studies have been suggested [62].…”
Section: Novel Evaluation Methodsmentioning
confidence: 99%
“…There are some attempts to consider non-sequential refinements to the pipeline model, such as that of Jansen and Dragicevic [28], who account for visualization beyond the desktop to include branching and merging. Parallel development at this scale is more commonly discussed at the ideation phase of visualization design [27] where the cost of prototyping multiple designs is comparatively small. Some work reports on successful use of parallel prototyping [15] to inform visualization design [20], however multiple designs tend to be merged or filtered ultimately to inform a single 'product' or analytical objective.…”
Section: Rethinking Visualization Design Modelsmentioning
confidence: 99%
“…• Critique: Holistic assessment of a human reading and interpretation of the visualization via "meticulous group discussion centered on how well particular aspects or details of a visualization support the intended goal" [19].…”
Section: Techniquesmentioning
confidence: 99%